Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis, biological evaluation and molecular docking studies of N-acylheteroaryl hydrazone derivatives as antioxidant and anti-inflammatory agents - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman; Gill, Charansingh H. (Research on Chemical Intermediates, 2016)
In search of new therapeutics with greater potency, three new series of 3-methyl-1-phenyl-1H-thieno[2,3-c]pyrazole-5-carbohydrazide derivatives have been synthesized and evaluated for their in vitro antioxidant and anti-inflammatory activities. The hydrazones bearing a core pyrazole, chromone and tetrazolo[1,5-a]quinoline scaffold showed promising activities. Interestingly, compounds 3a (EC50 = 06.00 +/- A 2.36) and 5c (EC50 = 07.21 +/- A 0.67) showed the most potent antioxidant activity, while compounds 3a (EC50 = 10.25 +/- A 1.08), 7b (EC50 = 10.50 +/- A 0.99) and 7c (EC50 = 11.18 +/- A 0.15) showed significant anti-inflammatory activity. Furthermore, molecular docking studies also revealed a significant correlation between the binding score and biological activity for these compounds to describe the molecular basis for the structure activity relationship (SAR) results. As these compounds are good cyclooxygenase inhibitors, isoenzyme inhibitory potency studies are warranted.
Keywords: Anti-inflammatory; Antioxidant; Docking study; N-Acylhydrazones; Structure-activity relationship

Tetrazoloquinoline-1,2,3-triazole derivatives as antimicrobial agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Akolkar, Satish V.; Nagargoje, Amol A.; Khedkar, Vijay M.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
In search of new active molecules, a small focused library of tetrazoloquinoline-based 1,2,3-triazoles has been efficiently preparedviaclick chemistry approach. Several derivatives were found to be exhibiting promising antimicrobial and antioxidant activity characterized by their lower minimum inhibitory concentration values. All the synthesized compounds exhibited excellent antibacterial activity against Gram negative bacteriaE. coliandF. devoransand antifungal activity againstC. albicansandA. niger. Further, these compounds were tested for their antitubercular activity against dormantMTB H37Raand dormantM. bovis BCGusing XRMA assay protocol and showed no significant activity. Also, the synthesized compounds were found to have potential antioxidant activity with IC(50)range = 12.48-50.20 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against the active site of fungalC. albicansenzyme P450 cytochrome lanosterol 14 alpha-demethylase, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of thein vitroandin silicostudy suggest that the triazole-incorporated tetrazoloquinolines may possess the ideal structural requirements for further development of novel therapeutic agents.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Docking study